2004
DOI: 10.1049/sb:20045013
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of design principles in biochemical networks

Abstract: Computer modelling and simulation are commonly used to analyse engineered systems.Biological systems differ in that they often can not be accurately characterized, so simulations are far from exact. Nonetheless , we argue in this paper that evolution results in recurring, dynamic organizational principles in biological systems, and that simulation can help to identify them and analyse their dynamic properties. As a specific example, we present a dynamic model of the galactose utilization pathway in yeast, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 61 publications
(87 reference statements)
3
38
0
Order By: Relevance
“…Based on our results we suggest that, as the sequestration of Gal80 protein proceeds, GAL7 and GAL10 transcription ensues first, followed by GAL1. This temporal expression pattern ensures that toxicity due to the accumulation of galactose-1-phosphate (De Atauri et al 2004) does not occur at any time during induction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results we suggest that, as the sequestration of Gal80 protein proceeds, GAL7 and GAL10 transcription ensues first, followed by GAL1. This temporal expression pattern ensures that toxicity due to the accumulation of galactose-1-phosphate (De Atauri et al 2004) does not occur at any time during induction.…”
Section: Discussionmentioning
confidence: 99%
“…The model used is as described in our previous study [38], except as indicated here. For the mutant strain, we modified the fractional saturation for GAL3 and GAL80 to a fixed value of 0.04.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. (2) was derived manually from the literature [15]. Accompanying this figure are biochemical and mathematical descriptions, which uniquely and unambiguously define the nature of the interactions within this system and the resulting dynamic behavior.…”
Section: Higher-level Abstractions Need a Functional Basismentioning
confidence: 99%